1995
DOI: 10.1074/jbc.270.41.24475
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Mechanism of the Berberine Bridge Enzyme, a Covalently Flavinylated Oxidase of Benzophenanthridine Alkaloid Biosynthesis in Plants

Abstract: The berberine bridge enzyme ((S)-reticuline:oxygen oxidoreductase (methylene-bridge-forming), EC 1.5.3.9) catalyzes the oxidative cyclization of the N-methyl moiety of (S)-reticuline into the berberine bridge carbon, C-8, of (S)-scoulerine. This is a reaction that has neither an equivalent in organic chemistry nor a parallel in nature. The uniqueness of this catalytic reaction prompted an in depth study that began with the isolation of the cDNA encoding the berberine bridge enzyme followed by the overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
125
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 26 publications
(40 reference statements)
10
125
0
6
Order By: Relevance
“…2% during prolonged incubation times) arise in the conversion of the substrate analog (S)-N-methylcoclaurine (10) 2 , which also lacks the C3'-OH group. This finding is considered supporting evidence for the two-step mechanism 2 . In light of our results with laudanosine and 8, however, it could also be explained by the formation of the intracyclic imine, followed by tautomerisation and hydrolytic demethylation to yield formaldehyde and (S)-coclaurine (11).…”
Section: Berberine Bridge Enzyme (Bbe) Catalyzes the Conversion Of (Smentioning
confidence: 52%
See 2 more Smart Citations
“…2% during prolonged incubation times) arise in the conversion of the substrate analog (S)-N-methylcoclaurine (10) 2 , which also lacks the C3'-OH group. This finding is considered supporting evidence for the two-step mechanism 2 . In light of our results with laudanosine and 8, however, it could also be explained by the formation of the intracyclic imine, followed by tautomerisation and hydrolytic demethylation to yield formaldehyde and (S)-coclaurine (11).…”
Section: Berberine Bridge Enzyme (Bbe) Catalyzes the Conversion Of (Smentioning
confidence: 52%
“…1a) 1 . This cyclization reaction has no known equivalent in organic chemistry and is proposed to proceed via a two step process starting with oxidation of the Nmethyl group to the corresponding iminium ion followed by an ionic ring closure initiated by the deprotonated C3'-OH group of the benzyl moiety 2 . This hydroxyl group apparently plays an important role for the enzymatic reaction, as substrate analogs lacking this group are not processed by the enzyme 2 .…”
Section: Berberine Bridge Enzyme (Bbe) Catalyzes the Conversion Of (Smentioning
confidence: 99%
See 1 more Smart Citation
“…Protoberberines, protopines and sanguinarine (S)-Scoulerine, the branch-point intermediate leading to protoberberine alkaloids, is formed from (S)-reticuline by BBe (Dittrich and Kutchan 1991;Facchini et al 1996;Kutchan and Dittrich 1995;winkler et al 2006). (S)-Scoulerine is converted via methylenedioxy bridge formation and O-methylation to a variety of protoberberines including (S)-canadine, (S)-stylopine and (S)-sinactine.…”
Section: Morphinementioning
confidence: 99%
“…Examination of the best characterized of the BBEs (Kutchan and Dittrich, 1995) revealed that these proteins contain a conserved, covalently bound FAD moiety that is required for activity. The translated NEC5 sequence also contains a homologous consen- sus flavin-binding domain (Fig.…”
Section: Characterization Of Nec5 As a Flavoproteinmentioning
confidence: 99%